Helical Polybissilsesquioxane Bundles Prepared Using a Self‐Templating Approach. Issue 1 (6th October 2015) - Wang, Qingfeng; Lin, Shuwei; Qin, Jiaming; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract: Polybissilsesquioxanes with single‐handed helical morphologies attracted much attention during the last decade, which could be applied as asymmetric catalysts and chiral stationary phases. Herein, a pair of chiral biphenylene‐bridged bissilsesquioxanes were synthesized. They self‐assembled into helical bundles in ethanol, behavior that was confirmed in field emission scanningelectron microscopy images. Circular dichroism analysis indicated that the biphenylene groups twisted in a single‐handed fashion. Single‐handed helical polybissilsesquioxane bundles were prepared via polycondensation of the bissilsesquioxanes, using a self‐templating approach. Because of the shrinkage that occurred during polycondensation, the helical pitches of the bundles were shorter than those of their corresponding organic self‐assemblies. The wide‐angle X‐ray diffraction pattern indicated that there were no π–π interactions among the diphenylene groups. The circular dichroism spectra indicated that the chirality was successfully transferred from the bissilsesquioxane self‐assemblies to the polybissilsesquioxane. The polybissilsesquioxanes displayed a capacity for the adsorption of nitrobenzene and had potential application for enantioseparation. Chirality 28:44–48, 2016 . © 2015 Wiley Periodicals, Inc. Abstract : Single‐handed helical polybissilsesquioxane bundles with optical activity are prepared through a self‐templating approach.